Impact of Perioperative Lidocaine on Neutrophil Extracellular Trapping and Serum Cytokines in Robot-Assisted Radical Prostatectomy: Randomized Controlled Study - Dongho Shin; Jiheon Kim; Subin Lee; Min Suk Chae (Medicina)
Background and Objective: This randomized controlled trial investigated the influence of perioperative lidocaine administration on the postoperative inflammatory response in patients undergoing robot-assisted radical prostatectomy, with the results having potential implications for postoperative recovery and cancer recurrence via neutrophil extracellular trapping (NETosis). Materials and Methods: In total, 58 patients with localized prostate cancer were randomly assigned to receive an intravenous infusion of 2% lidocaine or a saline placebo intraoperatively. Serum levels of interleukin (IL)-6, IL-10, and IL-17, tumor necrosis factor(TNF)-α, interferon(IFN)-γ, neutrophil elastase (NE), citrullinated histone3 (CitH3), and myeloperoxidase (MPO) were determined preoperatively and at 24 h postoperatively. Biochemical recurrence (BCR) was assessed over a follow-up period of 2 years. Results: The lidocaine group showed a significant change in MPO, a greater reduction in IL-10 level, and a smaller increase in the NE level compared to the placebo group, suggesting a modulatory effect of lidocaine on certain anti-inflammatory and neuroendocrine pathways. No significant difference in the BCR rate was observed between the two groups. Conclusions: Perioperative lidocaine administration selectively modulates certain inflammatory and neuroendocrine responses after robot-assisted radical prostatectomy surgery, potentially influencing recovery outcomes. These findings highlight the need for further investigations of the role of lidocaine in Enhanced Recovery After Surgery protocols, particularly in oncologic surgeries.